REL-BASED PUBLIC TRANSPORTATION COMPANY PUBLIC RELATIONS COMMUNICATION STRATEGY IN MAINTAINING IMAGE - Ilham Albar Pane; Taofik Hidayat; Agnita Ayucendika Damanik (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Rail-based public transportation companies face increasing demands for service quality and communication transparency, making public relations a strategic function in maintaining corporate image. This study aims to analyze the public relations communication strategies employed by rail-based public transportation companies to sustain their corporate image in the public sphere. The research adopts a qualitative approach using a case study method, with data collected through in-depth interviews with public relations practitioners, observation of communication activities, and analysis of corporate documents and communication materials. Data analysis was conducted using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that public relations communication strategies are implemented through systematic message planning that emphasizes information consistency, the utilization of multiple communication channels including conventional and digital media, and proactive relationship management with the media and key stakeholders. In addition, public relations plays an important role in addressing public complaints and disseminating timely and transparent information during service disruptions to maintain public trust. The study concludes that the effectiveness of maintaining corporate image is influenced not only by the frequency of communication, but also by message credibility, responsiveness of public relations practices, and the alignment of communication strategies with the characteristics and expectations of rail transportation service users.